2002
DOI: 10.1103/physreva.65.021406
|View full text |Cite
|
Sign up to set email alerts
|

Correlated electron emission in laser-induced nonsequence double ionization of helium

Abstract: In this paper, we have investigated the correlated electron emission of the nonsequence double ionization (NSDI) in an intense linearly polarized field. The theoretical model we employed is the semiclassical rescattering model, the model atom we used is the helium. We find a significant correlation between magnitude and direction of the momentum of two emission electrons, and give a good explanation for this striking phenomenon by observing the classical collisional trajectories. We argue that this correlation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
17
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 21 publications
3
17
0
1
Order By: Relevance
“…Only recent semi-classical calculations [12] were able to predict a similar pattern as observed. There, the first electron is set free with a velocity To further elucidate electron emission in NS double ionization of Ne, electron energy distributions are shown in Fig.2 In comparison, the electron energy distribution in coincidence with double ionization is significantly less steep, extending to much higher energies.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Only recent semi-classical calculations [12] were able to predict a similar pattern as observed. There, the first electron is set free with a velocity To further elucidate electron emission in NS double ionization of Ne, electron energy distributions are shown in Fig.2 In comparison, the electron energy distribution in coincidence with double ionization is significantly less steep, extending to much higher energies.…”
mentioning
confidence: 72%
“…Only recently, a new generation of differential measurements [3,4] along with various quantum [5][6][7][8][9][10] as well as classical calculations [11,12] provided convincing evidence that the so-called "rescattering" or recollision scenarioone of the three NS double ionization pathways (beyond collective tunneling, and shake-off) which have been proposed in the past -is the dominating mechanism. Here, one electron is ionized via tunneling, accelerated in the oscillating laser field and, under certain conditions, driven back to its parent ion knocking out another electron.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16]). Surprisingly, however, at PW/cm 2 intensities, where recollision is now being generally accepted [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] to dominate non-sequential double ionization, only few differential electron emission studies can be found in the literature for single ionization by femtosecond pulses in the optical frequency regime [17][18][19][20][21][22]. Here, at typical Keldysh [23] parameters γ = (I P /2U P )½ << 1 (I P : ionization potential; U P = I/(2ω) 2 : ponderomotive potential with I the laser intensity and ω its frequency; atomic units are used throughout), the photoelectron spectra become increasingly smooth and unstructured, whereas they display a confusingly rich structure at lower intensities for γ ≥ 1.…”
mentioning
confidence: 99%
“…Fueled by results of novel many-particle imaging techniques [1,4] recent interest in intense laser-atom interaction has increasingly focused to the investigation of many-electron transitions like double and multiple ionization, experimentally [2][3][4][5][6][7][8][9] as well as theoretically (see e.g. [9][10][11][12][13][14][15][16]). Surprisingly, however, at PW/cm 2 intensities, where recollision is now being generally accepted [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] to dominate non-sequential double ionization, only few differential electron emission studies can be found in the literature for single ionization by femtosecond pulses in the optical frequency regime [17][18][19][20][21][22].…”
mentioning
confidence: 99%